Unearthing the Ecology of Soil Microorganisms Using a High Resolution DNA-SIP Approach to Explore Cellulose and Xylose Metabolism in Soil - Pepe-Ranney, Charles; Campbell, Ashley N.; Koechli, Chantal N.; Berthrong, Sean; Buckley, Daniel H. (Frontiers in Microbiology, 2016)
We explored microbial contributions to decomposition using a sophisticated approach to DNA Stable Isotope Probing (SIP). Our experiment evaluated the dynamics and ecological characteristics of functionally defined microbial groups that metabolize labile and structural C in soils. We added to soil a complex amendment representing plant derived organic matter substituted with either 13C-xylose or 13C-cellulose to represent labile and structural C pools derived from abundant components of plant biomass. We found evidence for 13C-incorporation into DNA from 13C-xylose and 13C-cellulose in 49 and 63 operational taxonomic units (OTUs), respectively. The types of microorganisms that assimilated 13C in the 13C-xylose treatment changed over time being predominantly Firmicutes at day 1 followed by Bacteroidetes at day 3 and then Actinobacteria at day 7. These 13C-labeling dynamics suggest labile C traveled through different trophic levels. In contrast, microorganisms generally metabolized cellulose-C after 14 days and did not change to the same extent in phylogenetic composition over time. Microorganisms that metabolized cellulose-C belonged to poorly characterized but cosmopolitan soil lineages including Verrucomicrobia, Chloroflexi and Planctomycetes.